Man and Image (Training and Practice : Journal of Educational Sciences, 2014)
Image already appears int he life of man int he prehistoric period, preceeding the world. The man of that period used cave paintings in an effort to influence reality and determine future. In our days the magic seems to become real – even if not fully, not in its magical content. Technical images – as opposed to traditional pictures created with graphics or painting techniques – make us believe that they are unable to lie and are objective. Whoever experiences the world though them, experiences the world in a megical way, which leads to a programmed behaviour. The huge amount of violence present on TV is also reflected in children’s drawings, but what is more frightening than this is the fact there is proved immediate and straight correlation between the violence watched ont he screen and the cobsequent agressive behaviour. I think that in Hungary visual education has the biggest chance to teach about visual messages, visual sign systems and their mode of action.